Bones unearthed! - Hollihan, Kerrie Logan (Creepy and true, 2021)
"Discover all the mysteries, facts, and discoveries about skeletons that are creepy-and true-in the much-anticipated companion to Mummies Exposed! and Ghosts Unveiled! The Creepy and True series explores strange phenomena, fun facts, and out of the ordinary discoveries. Have you ever wondered what lies beneath our feet? Bones have a story to tell-and not always a happy one. Bones Unearthed!, book 3 of the Creepy and True series, investigates remarkable discoveries of skeletal remains and what they reveal about human civilization. Combining fascinating history with science, award-winning author Kerrie Logan Hollihan unearths the truth about famous bones by exploring forensic evidence, archaeology, anthropology, medicine, and folklore. Meticulously researched and respectful, yet light and humorous in tone, these cryptic tales of murder and mayhem span across cultures and millennia, covering everything from Aztec skull racks, the cannibals of Jamestown, and Benjamin Franklin's basement boneyard, to frozen sailors in the Arctic and the centuries-long search for the body of King Richard III. From cemeteries to laboratories to excavation sites around the world, Bones Unearthed! digs deep into the graves of the dearly departed. For readers who can't get enough of the macabre, this quirky nonfiction narrative will disturb and delight. Includes color illustrations throughout, as well as endnotes, bibliography, and index"--